Post-traumatic stress disorder among heart disease patients: a clinical follow-up of individuals with myocardial infarction in the Tromsø Study ... - Lorem, Geir Fagerjord; Næss, Eva T.; Løchen, Maja-Lisa; Lillevoll, Kjersti; Molund, Else-Marie; Rösner, Assami; Lindkvist, Sigmund; Schirmer, Henrik (figshare, 2023)
Abstract Background Myocardial infarction is likely to be experienced as a life-threatening and potentially traumatic event. Approximately one-third of patients with myocardial infarction experience clinically significant symptoms of anxiety/depression. However, it is unclear how many of these patients experience these symptoms because of post-traumatic stress disorder (PTSD). We conducted a clinical screening of individuals with a confirmed myocardial infarction diagnosis. Our goal was to examine the prevalence of PTSD in myocardial infarction patients and study how PTSD symptoms were associated with exposure to potentially traumatic events. Method This is epidemiological research with a cross-sectional design following up participants from the Tromsø Study with a confirmed diagnosis of myocardial infarction. We sent invitations to participants in the Tromsø Study with clinically significant self-reported anxiety or depression symptoms following myocardial infarction. A cross-sectional sample of N = 79 ...